2021
DOI: 10.1093/pubmed/fdab134
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of medicine take-back concept at community level in Nepal: a pilot study

Abstract: Background Most households may have leftover, unwanted, unused and expired (UUE) medicines. The present research aimed to analyze feasibility of implementation of medicine take-back in select communities in Nepal. Methods Exploratory (i.e. feasibility) study was conducted among 400 adults from July 2017 to January 2018. Study sites and participants were selected by simple random sampling and respondents were interviewed about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Take-back concept could be initiated and implemented on government funding or other sources. 34 Only one-fifth (20.4%) of HCPs had a good practice of disposal of unused, unwanted and expired medicines in the present study. JRs (25.1%) had a better practice than faculties (15.8%) and it was statistically significant (p=0.048).…”
Section: Us-food and Drug Administration (Fda) And Nepalesementioning
confidence: 53%
“…Take-back concept could be initiated and implemented on government funding or other sources. 34 Only one-fifth (20.4%) of HCPs had a good practice of disposal of unused, unwanted and expired medicines in the present study. JRs (25.1%) had a better practice than faculties (15.8%) and it was statistically significant (p=0.048).…”
Section: Us-food and Drug Administration (Fda) And Nepalesementioning
confidence: 53%
“…Following HICs, collaboration between national drug regulatory authorities and ministries responsible for opioid regulations in LMICs, together with the police, drug stores, and local pharmacies, is crucial in managing unused, unwanted and expired medication for safe disposal as well as discouraging illegal opioid distribution. A pilot study to confirm the implementation of the drug take-back concept within the communities of an LMIC concluded that the participants were eager to support the program if implemented; however, the major challenge could be an allocation of budget from the government (Sapkota et al, 2022 ).…”
Section: Opioid Stewardship Strategiesmentioning
confidence: 99%